Pacific Biological Laboratory - Ed Ricketts, Junior:::Creator:::
Pacific Biological Laboratory, 800 Cannery Row, Monterey, California. From left to right: Ed 'Doc' Ricketts, William Alston Ritchie Lovejoy (1908-1956), Toni Jackson, John Lovejoy. Toni Jackson lived with Ed. Ricketts for seven years.